2016
DOI: 10.18240/ijo.2016.09.20
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of optic disc damage by optical coherence tomography in terms of therapy in non-arteritic anterior ischemic optic neuropathy

Abstract: This study aimed to assess the relationship between the rate of nerve fiber loss in non-arteritic anterior ischemic optic neuropathy (NAION) and time delay before therapy. Total 24 patients received the same treatment within or after 2wk (early and late groups). There were significantly lower level of destruction of nerve fibers (P=0.0014) and significantly better visual field sensitivity (P=0.039) in early group. The results indicate that therapy should be started within 2wk. The degree of ischemic damage due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Some recent studies have demonstrated the use of OCT in the assessment, diagnosis, and management of NAION. 6 , 20 Findings include increased peripapillary choroidal thickness associated with optic disc edema and subretinal fluid on spectral domain OCT (SD-OCT) and macular ganglion cell inner plexiform layer thinning associated with VF defect in frequency domain OCT (FD-OCT). 6 , 21 Another study found that NAION affected neither the cup-to-disc ratio nor alpha or beta zone of parapapillary atrophy.…”
Section: Management and Treatmentmentioning
confidence: 99%
“…Some recent studies have demonstrated the use of OCT in the assessment, diagnosis, and management of NAION. 6 , 20 Findings include increased peripapillary choroidal thickness associated with optic disc edema and subretinal fluid on spectral domain OCT (SD-OCT) and macular ganglion cell inner plexiform layer thinning associated with VF defect in frequency domain OCT (FD-OCT). 6 , 21 Another study found that NAION affected neither the cup-to-disc ratio nor alpha or beta zone of parapapillary atrophy.…”
Section: Management and Treatmentmentioning
confidence: 99%